Upaya Meningkatkan Hasil Belajar Materi Menggiring dan Mengumpan Menggunakan Pendekatan Permainan Gobak Sodor - Harpanurrozi, Lalu (Lembaga Yasin AlSys, 2022)
The purpose of this study was to improve the learning outcomes of dribbling and baiting the ball using the Gobak Sodor Game Approach for Class VIIB Students of SMPN 10 Mataram. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and reflection. Based on the results of action research that the Gobak Sodor Game Approach can Improve Learning Outcomes in Herding and Feeding the Ball for Class VIIB Students of SMPN 10 Mataram. Furthermore, the researcher recommends: (1) Teachers who have the same difficulties can apply the Gobak Sodor Game Approach to improve learning outcomes. (2) In order to get maximum results, it is hoped that the teacher will make the Gobak Sodor Game Approach more interesting and varied.